Los orígenes de la Revolución francesa : la toma de la Bastilla (14 de Julio de 1789) / Jacques Godechot ; [traducción de María L. y Rosa M. Feliu] - Godechot, Jacques (Historia, ciencia, sociedad ; 108)
Bibliografía: p. 353-373